2020
DOI: 10.1002/adsc.201901195
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)‐Catalyzed Enantioselective C−H Alkenylation of Ferrocenecarboxylic Acid

Abstract: The palladium‐catalyzed enantioselective C−H alkenylation of ferrocenecarboxylic acid has been developed. A series of 2‐alkenyl ferrocenecarboxylic acids with planar chirality were obtained using molecular oxygen as an oxidant. This protocol starts from less expensive and readily available starting materials and provides the target products as a key intermediate in organic synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 82 publications
0
14
0
1
Order By: Relevance
“…Apart from the development of dialkylaminomethyl as a suitable directing group, other directing groups were less investigated for the Pd(II)-catalyzed asymmetric C-H functionalization of ferrocenes. Until recently, the carboxylic acid was identified as a weakly coordinating directing group in the Pd-catalyzed ortho-alkenylation reaction reported by Wu, Cui, and coworkers, providing planar chiral 1,2-disubstituted ferrocenecarboxylic acid derivatives (Figure 2G) [70]. This reaction proceeded smoothly by using oxygen as the oxidant in good yields and enantioselectivity.…”
Section: Pd(ii)-catalyzed Asymmetric C-h Bond Functionalization Of Ferrocenesmentioning
confidence: 93%
“…Apart from the development of dialkylaminomethyl as a suitable directing group, other directing groups were less investigated for the Pd(II)-catalyzed asymmetric C-H functionalization of ferrocenes. Until recently, the carboxylic acid was identified as a weakly coordinating directing group in the Pd-catalyzed ortho-alkenylation reaction reported by Wu, Cui, and coworkers, providing planar chiral 1,2-disubstituted ferrocenecarboxylic acid derivatives (Figure 2G) [70]. This reaction proceeded smoothly by using oxygen as the oxidant in good yields and enantioselectivity.…”
Section: Pd(ii)-catalyzed Asymmetric C-h Bond Functionalization Of Ferrocenesmentioning
confidence: 93%
“…Acid directed olefination of ferrocene carboxylic acid 17 has been developed by Wu and co-workers to synthesize 1,2-disubstituted ferrocene carboxylic acids 18 with planar chirality using the chiral MPAA ligand N -Ac-L-Phe-OH ( Scheme 9 ). 17 Diverse alkenes such as acrylates, acrylamides, vinyl phosphates, vinyl ketones and styrenes were tolerated under the given reaction conditions. Ferrocenium ion was formed in the presence of oxygen and served as the terminal oxidant to regenerate Pd( ii ) from Pd(0).…”
Section: Proximal C(sp 2 )–H Olefinationmentioning
confidence: 96%
“…36 In 2020, a Pd(II)-catalyzed enantioselective C-H alkenylation of weakly coordinated ferrocenecarboxylic acid using Ac-L-Phe-OH as the chiral ligand was reported by the same group (Scheme 14c). 37 Very recently, the Hou group synthesized a chiral half-sandwich scandium catalyst Ph-TMS-Sc, which was employed in an enantioselective C-H alkenylation of ferrocenes with internal alkynes to synthesize various N/alkene-functionalized planar chiral ferrocenes 55 in high yields with excellent enantioselectivities (Scheme 15). 38 The deuterium-labelling experiments suggested that C-H activation could also take place at the C8 position of quinoline moiety, even though the alkyne insertion only occurred at the Cp ring of ferrocene.…”
Section: Alkenylationmentioning
confidence: 99%